KERATON DEMAK BINTORO MEMBANGUN TRADISI ISLAM MARITIM DI NUSANTARA - Heru Arif Pianto (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2017)
Kingdom of Demak is the oldest Islamic kingdom in Java. In addition Bintoro Demak Sultanate is also an area where the pedagn anchored link from various directions. Traders anchored while utilizing Demak as a transit point and peddle copies merchandise. In addition Demak is also supported by geography high potential to develop maritime culture. Even when the days of the kingdom of Demak Duke Unus very advanced, even with the Duke Unus effort that attack invaders to cross the sea, even referred to as Prince maritime. It is sufficient evidence that marine science is already well developed. This research is historical. While the methods used in this research is the method of historical research, consisting of four steps, ie, heuristic, criticism, interpretation and historiography. The results showed that as the maritime kingdom of Demak perform its function as a link and transit between producing spices in eastern Indonesia and the Malacca as a market in western Indonesia. That's why an initiative arising from Demak ruler of Malacca to manggantikan position as a trading center, both nationally and internationally. To realize all this, we intend to occupy Malacca Demak Bintoro advance to expel the Portuguese who has been in power since 1511 AD. The effort was made when in 1511 AD, Demak under the leadership of Duke Unus voyage to Malacca hold together his forces to carry out a massive attack against the Portuguese, although no results.Keywords : Islamic tradition, Maritime, Nusantara